2022
DOI: 10.1136/bmj-2021-067731
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of statins on non-high density lipoprotein cholesterol in people with diabetes and at risk of cardiovascular disease: systematic review and network meta-analysis

Abstract: ObjectiveTo compare the efficacy of different statin treatments by intensity on levels of non-high density lipoprotein cholesterol (non-HDL-C) for the prevention of cardiovascular disease in people with diabetes.DesignSystematic review and network meta-analysis.Data sourcesMedline, Cochrane Central Register of Controlled Trials, and Embase from inception to 1 December 2021.Review methodsRandomised controlled trials comparing different types and intensities of statins, including placebo, in adults with type 1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…The results of five trials assessing the effectiveness of statins in COVID-19 have been reported so far. Statins are the first line of treatment for dyslipidemia and their effectiveness in improving lipid profile has been well-proven in the past [ 33 ]. In addition to their lipid-lowering effects, previous studies found statins to be potentially beneficial in preventing and treating infections [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of five trials assessing the effectiveness of statins in COVID-19 have been reported so far. Statins are the first line of treatment for dyslipidemia and their effectiveness in improving lipid profile has been well-proven in the past [ 33 ]. In addition to their lipid-lowering effects, previous studies found statins to be potentially beneficial in preventing and treating infections [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of statins in the primary and secondary prevention of ischaemic cardio-cerebrovascular diseases has also been well proved 4 5. Many studies have demonstrated that statin can reduce primary and secondary cardiovascular events 6–10. Several studies have also demonstrated that there was an association between statin use and reduced mortality in patients with ICH 11–13.…”
Section: Introductionmentioning
confidence: 99%
“…4 5 Many studies have demonstrated that statin can reduce primary and secondary cardiovascular events. [6][7][8][9][10] Several studies have also demonstrated that there was an association between statin use and reduced mortality in patients with ICH. [11][12][13] However, others reported that this relationship did not exist.…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia in diabetes patients is characterized by increased levels of non-high-density lipoprotein cholesterol (non-HDL-C), including low-density lipoprotein cholesterol (LDL-C), intermediate-density lipoprotein, and very low-density lipoprotein remnants, all of which contribute to the development of atherosclerosis [10,11]. In recent years, the clinical value of non-HDL-C has gained widespread attention and recognition.…”
Section: Introductionmentioning
confidence: 99%